2019
DOI: 10.1016/j.heliyon.2019.e02496
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of MHD double diffusive natural convection and entropy generation in a wavy enclosure filled with nanofluid with discrete heating

Abstract: A numerical investigation of entropy generation, heat and mass transfer is performed on steady double diffusive natural convection of water-based Al2O3 nanofluid within a wavy-walled cavity with a center heater under the influence of an uniform vertical magnetic field. The top horizontal wavy wall, left and right vertical walls of the enclosure are kept at low temperature and concentration of Tc and cc whereas central part of the bottom horizontal wall is maintained at high temperature and concentration of Th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…where 1 , 2 and 3 are irreversibility distribution ratios and they are taken as 1 = 0.0001, 2 = 0.5 and 3 = 0.01 ( [22]).…”
Section: Entropy Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…where 1 , 2 and 3 are irreversibility distribution ratios and they are taken as 1 = 0.0001, 2 = 0.5 and 3 = 0.01 ( [22]).…”
Section: Entropy Generationmentioning
confidence: 99%
“…According to the local thermodynamic equilibrium of linear transport theory, the dimensionless local entropy generation due to fluid friction, heat transfer, mass transfer and magnetic field in Cartesian coordinate are given by (see, [30] and [31] ) where , and are irreversibility distribution ratios and they are taken as 0.0001 0.5 and 0.01 ( [22] ).…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was extensively used in modern heat exchangers applicated in steam generation, condensation in power and cogeneration plants, chemical and agricultural products, automobile industry, etc. [44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. Hasanuzzamana et al 2007 [44], studied the natural convection in a square cavity having two V-wavy parallel vertical plates and two flat horizontal plates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Alhashash and Saleh 35 treated the porous media using Darcy model and found that the thermal performance were sensitive to the varying of corrugation property, Rayleigh number and nanoparticle volume fraction. Parveen and Mahapatra 36 studied double diffusive free convection in a wavy enclosure filled with nanofluid under partial heating. Free convection in a heat generating porous medium-filled wavy enclosures using Buongiorno’s nanofluid model was investigated by Ahmed and Rashed.…”
Section: Introductionmentioning
confidence: 99%